2017
DOI: 10.12659/ajcr.905787
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of the Inferior Vena Cava in an HIV-Positive Adult Patient: A Case Report and Review of the Literature

Abstract: Patient: Female, 64Final Diagnosis: IVC leiomyosarcomaSymptoms: Back pain • leg pain • leg swellingMedication: —Clinical Procedure: IVC filter placement • CT-guided IVC mass biopsySpecialty: OncologyObjective:Rare diseaseBackground:Leiomyosarcoma is the most common primary malignancy of the inferior vena cava (IVC), and represents approximately 10% of primary retroperitoneal sarcomas. Leiomyosarcoma presents with non-specific symptoms, including abdominal pain or back pain. There is an increased incidence in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…[ 14 ] The etiology remains unclear, although it has been reported that LMS is highly probable in immunosuppressed patients (HIV-positive patients and organ transplant recipients). [ 15 ] In this case, the patient tested negative for HIV serology, and there was no significant medical evidence that indicated the possibility of immunosuppression. The histological variant of sarcoma does not provide sufficient information for planning therapy and predicting prognosis.…”
Section: Discussionmentioning
confidence: 93%
“…[ 14 ] The etiology remains unclear, although it has been reported that LMS is highly probable in immunosuppressed patients (HIV-positive patients and organ transplant recipients). [ 15 ] In this case, the patient tested negative for HIV serology, and there was no significant medical evidence that indicated the possibility of immunosuppression. The histological variant of sarcoma does not provide sufficient information for planning therapy and predicting prognosis.…”
Section: Discussionmentioning
confidence: 93%
“…Because of the lack of specificity, most of these techniques are considered non-diagnostic. The diagnosis of the IVC sarcoma is difficult, and due to the insidious course of the disease, and most cases are diagnosed at a late stage ( 16 ). The final diagnosis of the IVC leiomyosarcoma is based on pathology.…”
Section: Discussionmentioning
confidence: 99%
“…At present, radical surgical resection with free margins is believed to be the best curative therapy for the IVC leiomyosarcoma ( 14 , 16 , 19 ). The surgical approach differs depending on the tumor invasiveness and location, including simple tumor excision with IVC repair and tumor excision with graft replacement.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Since then, early aggressive surgical intervention has been the treatment of choice with roughly 600 reported cases globally as of 2017. 9 In the largest pooled analysis to date, Wachtel et al evaluated resection outcomes in 377 patients with surgical resection finding a low 30-day mortality of 1.9%, but 24.7% complication rate including lower extremity edema and acute renal failure but also bowel injury and hemorrhage. 4 In this cohort, disease-free survival and overall survival were 57% and 92% at one year and 6% and 55% at 5 years, respectively; however, the median overall survival was only 23 months.…”
Section: Discussionmentioning
confidence: 99%